2015
DOI: 10.1002/app.42558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil environment on the photo‐degradation of polyethylene films

Abstract: Outdoor weathering field trials performed with oxo-degradable polyethylene (PE) thin films were conducted across temperate, grassland, and subtropical sites around Australia. It was found that a site factor, that was apparently independent of total solar dose and temperature, significantly impacted the rate and extent of photo-oxidation. Controlled laboratory-based accelerated aging trials of both PE film with no prodegradant and oxo-degradable PE films (containing iron stearate) revealed that the rate and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In natural conditions, most often with the interaction of different types of degradation with different intensities of the impact of degradation factors occurs, which example is simultaneous impact of atmospheric (chemical and thermal degradation) and mechanical factors (mechanodegradation) on stadium seats during their use [12, 17 ÷ 19]. In turn, in this study, [32,33], it was found that the effect of many factors at the same time enhances the degradation processes. In publications [25,26] it was pointed out that polymeric materials are characterized by different resistance and behaviour during keeping in aggressive substances.…”
Section: Introductionmentioning
confidence: 64%
“…In natural conditions, most often with the interaction of different types of degradation with different intensities of the impact of degradation factors occurs, which example is simultaneous impact of atmospheric (chemical and thermal degradation) and mechanical factors (mechanodegradation) on stadium seats during their use [12, 17 ÷ 19]. In turn, in this study, [32,33], it was found that the effect of many factors at the same time enhances the degradation processes. In publications [25,26] it was pointed out that polymeric materials are characterized by different resistance and behaviour during keeping in aggressive substances.…”
Section: Introductionmentioning
confidence: 64%
“…The subject literature shows that previous studies focused primarily on the assessment of changes in the properties of various types of polymer materials in the composting process [14,64], after introducing into the soil [27,28] or on a simultaneous comparison of the composting process and the effect of the soil environment on the polymer material degradation [73]. Also Gauthier et al [74] and Vargla et al [75] emphasised the fact that the majority of previous tests to determine the degree of polymer material degradation were carried out under controlled conditions and that the information relating to natural conditions is very limited, as such tests usually concern the possibility of using polymer materials for agricultural crops under protective covers. Gauthier et al [74] argued that this is caused by the difficulty to determine the impact of individual environmental factors (e.g.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Also Gauthier et al [74] and Vargla et al [75] emphasised the fact that the majority of previous tests to determine the degree of polymer material degradation were carried out under controlled conditions and that the information relating to natural conditions is very limited, as such tests usually concern the possibility of using polymer materials for agricultural crops under protective covers. Gauthier et al [74] argued that this is caused by the difficulty to determine the impact of individual environmental factors (e.g. geographical location, weather conditions, use of fertilisers and plant protection products) on the rate of polymer material degradation.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene (PE) is one of the most extensively used thermoplastic polymers [1,2]; its mechanical properties, electrical insulation, chemical resistance, being odorless and nontoxic, toughness and flexibility, low cost, and easy processability have led to a widespread use in diverse applications [3,4]. These properties make PE suitable material for use as packaging films, enabling the production of mechanically strong films [5].…”
Section: Introductionmentioning
confidence: 99%